Sarcopenia is Associated with Poor Performance Status in Indonesian Patients with Hepatocellular Carcinoma - Koncoro, Hendra; Hasan, Irsan; Lesmana, C Rinaldi; Aditama, Humala Prika; Salamah, Thariqah; Rizka, Aulia; Wahyudi, Edy Rizal; Shatri, Hamzah; Teng, Wei (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Background: Sarcopenia has a notable impact on the prognosis of hepatocellular carcinoma (HCC). The prevalence of sarcopenia in patients with HCC is relatively high, with studies reporting rates between 39% and 41.7%. A substantial proportion of individuals diagnosed with HCC also exhibit muscle wasting and reduced muscle function. This study aims to determine the prevalence of sarcopenia in Indonesian patients with HCC (based on the Japanese Socuety of Hepatology (JSH) JSH criteria) and to examine its correlation with poor performance status.Methods: We performed a cross-sectional study of 85 HCC patients between January and October 2021). The skeletal muscle index at L3 (L3 SMI) was measured on CT scans (applying JSH cut-offs for sarcopenia). Clinical data, including Eastern Cooperative Oncology Group (ECOG) performance status, were collected. Bivariate analyses and logistic regression were performed to identify factors associated with sarcopenia.Results: A total of 85 HCC patients (median age: 52 years) were included in the analysis. Sarcopenia was observed in 49.4% of the cohort. Bivariate analysis revealed a statistically significant association between sarcopenia and an ECOG performance status of 2+ (p = 0.003), as well as a MELD-Na score of ≥15 (p = 0.023). In multivariate analysis, poor ECOG-PS remained independently associated with sarcopenia (adjusted OR 4.17; 95% CI 1.50–11.56, p = 0.006).Conclusion: Sarcopenia is highly prevalent among Indonesian HCC patients, and it is strongly associated with poor ECOG performance status.